2014
DOI: 10.1038/onc.2014.134
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-885-3p inhibits the growth of HT-29 colon cancer cell xenografts by disrupting angiogenesis via targeting BMPR1A and blocking BMP/Smad/Id1 signaling

Abstract: The previous studies in this lab discovered that microRNA-885-3p (miR-885-3p) was regulated by a sulfated polysaccharide that bound to bone morphogenetic protein receptor, type IA (BMPR1A) to inhibit angiogenesis. However, its specific role and its mechanism of action in tumor cells have not been elucidated. We show that miR-885-3p markedly suppresses angiogenesis in vitro and in vivo. MiR-885-3p inhibits Smad1/5/8 phosphorylation and downregulates DNA-binding protein inhibitor ID-1 (Id1), a proangiogenic fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 27 publications
2
37
0
Order By: Relevance
“…In recent studies, microRNA deregulations have been frequently observed and induce the pathogenesis of human colorectal cancers [16]. miR-374a, located on chromosome Xq13.2, promotes or suppresses development of human cancer according to different studies.…”
Section: Introductionmentioning
confidence: 99%
“…In recent studies, microRNA deregulations have been frequently observed and induce the pathogenesis of human colorectal cancers [16]. miR-374a, located on chromosome Xq13.2, promotes or suppresses development of human cancer according to different studies.…”
Section: Introductionmentioning
confidence: 99%
“…Using certain biology software, we find that Smad5 is also a target gene of miR-93. As suggested, bone morphogenetic protein (BMP)/Smad signaling pathway promote the vascular development [16]. As a key mediator of BMP/Smad pathway, Smad5 can act as a target of microRNA to suppress the endothelial development and thereby the angiogenesis, a must for tumor progression and tumor metastases [17, 18].…”
Section: Introductionmentioning
confidence: 99%
“…A total of 10 miRNAs were negatively correlated with TACC3 expression and qualified as having a binding site within the TACC3 mRNA 3′ untraslational region. Some of these miRNAs, such as miR-1224-5p [27], miR-30e-3p [28], miR-488-3p [29], miR-491-5p [30], miR-940 [31] and miR-885-3p [32], are proven as tumor suppressors for various cancers. In the CGGA miRNA dataset, these TACC3 negatively associated miRNAs were significantly downregulated in high grade glioma (except for miR-330-3p, p = 0.4164) (Figure S5).…”
Section: Resultsmentioning
confidence: 99%